MODERNISASI SISTEM PEMASYARAKATAN SEBAGAI SUB SISTEM PERADILAN PIDANA DI INDONESIA (STUDI ANALISIS SIYASAH QADHA’IYAH SYAR’IYAH) - Edi Rosman; Zul Efendi; Saiful Amin; Miswardi Miswardi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The panitentiary System in Indonesia in general and in West Sumatra in particular is a sub-Criminal Justice System. Goal orientation of the criminal process since the police, prosecutors, judiciary is a panitentiary. The philosophy’s is conceptually much different from the concept of imprisonment. The existence of a gap between the conceptual ideal and its practical reality, the planning and implementing the modernization process of both the system and the penitentiary itself. Penitentiary is